Penguatan Peran Majelis Permusyawaratan Rakyat Dalam Struktur Ketatanegaraan Indonesia - Nazriyah, R. (UI Scholars Hub, 2017)
Nevertheless, the amendment (fifth) should be done with wisdom, sincerity, deliberation, and After the constitutional amendment the Assembly's role was limited only on disseminate the results of the 1945 amendment and appoint President and Vice President. Strengthening the role of the Assembly now has begun to appear with the revival of the tradition of the annual session of the Assembly, with less in this way the performance of the President and other state institutions can be controlled and serve as checks and balances. Discourse to reuse the guidelines need to consider the following matters: first, it should be clearly who is authorized to make. Second, in what legal form the guidelines set forth? For that, it needs the affirmation of the matter and the legal status of consultative assembly within the Indonesian legal system, including provisional consultative assembly is still valid